Sleep slow oscillation and plasticity. (June 2017) - Timofeev, Igor; Chauvette, Sylvain
Highlights: During slow-wave sleep cortical activity is dominated by spindles and slow waves. During wake cortical network displays activated patterns. Overall sleep slow wave activity potentiates majority of cortical synapses. Abstract : It is well documented that sleep contributes to memory consolidation and it is also accepted that long-term synaptic plasticity plays a critical role in memory formation. The mechanisms of this sleep-dependent memory formation are unclear. Two main hypotheses are proposed. According to the first one, synapses are potentiated during wake; and during sleep they are scaled back to become available for the learning tasks in the next day. The other hypothesis is that sleep slow oscillations potentiate synapses that were depressed due to persistent activities during the previous day and that potentiation provides physiological basis for memory consolidation. The objective of this review is to group information on whether cortical synapses are up-scaled or down-scaled during sleep. We conclude that the majority of cortical synapses are up-regulated by sleep slow oscillation.